Hierarchical Engineering of Double‐Shelled Nanotubes toward Hetero‐Interfaces Induced Polarization and Microscale Magnetic Interaction - Liu, Panbo; Wang, Yi; Zhang, Guozheng; Huang, Ying; Zhang, Ruixuan; Liu, Xianhu; Zhang, Xuefeng; Che, Renchao (Advanced functional materials, 2022)
Hierarchical engineering of suitable dielectric‐magnetic multicomponents shows good performance for microwave absorbers, but still face bottlenecks. Herein, hierarchical double‐shelled nanotubes (DSNTs), in which the inner magnetic tubular subunits are assembled by magnetic‐heteroatomic components through cation‐exchange reactions, and the outer dielectric MnO2 nanosheets strengthen the synergistic interactions between confined heterogeneous interfaces are ingeniously designed and constructed. Hetero‐interfaces induced polarization is proposed to investigate the interfacial relaxation mechanism, and magnetic loss, closely related to the micrometer‐scale magnetic units, is mainly clarified by the magnetic interaction composed of magnetic coupling and magnetic diffraction; both of them are clearly confirmed by Lorentz off‐axis electron holography. The obtained hierarchical DSNTs demonstrate efficient microwave absorption with an optimal reflection loss of −54.7 dB and qualified absorption bandwidth of 9.5 GHz owing to desirable heterogeneous interfaces, multiple magnetic heteroatomic components and hollow hierarchical microstructures. This strategy inspires a generalized methodology for the engineering of hollow hierarchical configurations with multishells, the combination of proposed hetero‐interfaces induced polarization and microscale magnetic interaction broadens the dielectric‐magnetic synergistic mechanism of the topography–performance relationship for microwave absorption materials. In this work, the authors propose an ion exchange‐pyrolysis‐hydrothermal strategy to construct hierarchical double‐shelled nanotubes, in which inner magnetic tubular subunits are assembled by magnetic‐heteroatomic components and outer dielectric MnO2 nanosheets are randomly packed on the surface.